Revolutionary Suicide and Civil Disobedience: Huey P. Newton [Suicidio Revolucionario y Tradición de Desobediencia Civil: Huey P. Newton] - Neira-Barrera, H (Departamento de Literatura EspaÃÂ±ola-Universidad de Sevilla, 2022)
Our aim is to analyse the concept and the practice of revolutionary suicide, as it was conceived by Huey Pierce Newton, founder of the Black Panther Party for Self Defense. The historical-theoretical context of our work is some political revolutionary self-sacrificial theories, which stablish the difference and the link between Newton and other conceptions of civil resistance. We focus in Newton s collection of essays entitled The Huey P. Newton Reader (1970) and in his autobiography, Revolutionary Suicide (1973). The concept of revolutionary suicide has been scarcely developed and it was absent in the special issue about the Black Panther Party published in 2017 by the Journal of African American Studies. Our conclusion is that Newton was a leader with a complex intellectual inspiration, from Plato to Fanon. Revolutionary self-sacrifice is the key that allows him to embrace, renew and transmit a specific theoretical inflexion of civil resistance, which also stems from some authors who are rarely quoted by him. © 2022 Departamento de Literatura EspaÃƒÂƒÃ‚Â±ola-Universidad de Sevilla. All rights reserved.